Polymorphisms in the HSF2, LRRC6, MEIG1 and PTIP genes correlate with sperm motility in idiopathic infertility. (29th June 2022) - Gupta, Nishi; Sarkar, Saumya; Mehta, Poonam; Sankhwar, Satya Narayan; Rajender, Singh
Abstract: The aim of this study was to investigate the association of 24 functionally important single nucleotide polymorphisms (SNPs) with male infertility. In this cross‐sectional study, we genotyped 24 functionally important single nucleotide polymorphisms in 24 infertility candidate genes in 500 oligo‐/astheno‐/oligoastheno‐/normo‐zoospermic infertile men with idiopathic infertility. Sequenom iPlex gold assay was used for genotyping. Sperm count and motility were compared between prevalent genotypes at each test locus. We did not observe any significant difference in the average sperm count between the alternate genotypes for the loci in the KLK3, LRRC6, MEIG1, HSF2, ESR2 and PTIP genes . However, we observed a significant difference in sperm motility between the alternate genotypes for the loci in the LRRC6, MEIG1, HSF2 and PTIP genes. Polymorphisms in the LRRC6 (rs200321595), MEIG1 ( rs150031795), HSF2 ( rs143986686) and PTIP (rs61752013) genes show association with sperm motility.